HAKEKAT ISTBAT NIKAH TERHADAP SAHNYA STATUS PERKAWINAN - Widhy Andrian Pratama; Adis Nevi Yuliani (Sekolah Tinggi Ilmu Syariah Darul Falah Bondowoso, 2024)
Marriage is a form of obedience to Allah. Marriage is a strong bond between husband and wife and descendants, a relationship that in life and life is a sacred combination and high quality habits in human development as a gift from God. This registration is important, as proof of the validity of a marriage which is proven by a marriage certificate, if something happens during the marriage then legal action can be taken, in order to maintain or obtain the rights of each husband and wife because with the marriage certificate the husband and wife have authentic evidence of legal actions. what they have done. Because marriage can only be proven by a marriage certificate made by a marriage registrar. The results of the research show that Istbat nikah can help the community in obtaining legal certainty from religious courts, especially regarding whether or not a marriage between a husband and his wife is valid.